2016
DOI: 10.20944/preprints201612.0113.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breast Cancer Brain Metastases: Clonal Evolution in Clinical Context

Abstract: Brain metastases are highly-evolved manifestations of breast cancer arising in a unique microenvironment, giving them exceptional adaptability in the face of new extrinsic pressures. The incidence is rising in line with population ageing, and use of newer therapies that stabilise metastatic disease burden with variable efficacy throughout the body. Historically, there has been a widely-held view that brain metastases do not respond to circulating therapeutics because the blood-brain-barrier (BBB) restricts the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Micrometastasis to brain is detected in ~30% of mice within 1 month of xenografting DCIS cells induced to express high levels of SOX11. SOX11 is amplified and overexpressed in ~30% of brain metastases in a recent study of a small cohort of breast cancer patients that were profiled using an integrated genomic and transcriptomic analysis of fresh frozen tumour samples ( Saunus et al, 2017 ; Saunus et al, 2015 ) and highly expressed by ~30% of BCBM in another independent study ( Varešlija et al, 2019 ). Our finding that iSOX11 mammary tumours spontaneously metastasize to the brain is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Micrometastasis to brain is detected in ~30% of mice within 1 month of xenografting DCIS cells induced to express high levels of SOX11. SOX11 is amplified and overexpressed in ~30% of brain metastases in a recent study of a small cohort of breast cancer patients that were profiled using an integrated genomic and transcriptomic analysis of fresh frozen tumour samples ( Saunus et al, 2017 ; Saunus et al, 2015 ) and highly expressed by ~30% of BCBM in another independent study ( Varešlija et al, 2019 ). Our finding that iSOX11 mammary tumours spontaneously metastasize to the brain is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The technical and clinical advantages and disadvantages of xenografts and genetically engineered mouse models as well as combinational breast cancer models have recently been reviewed by Holen et al Studies are also exploring the use of microfluidic devices for 3D breast tumor models to better mimic the physiological microenvironment in vitro . However, current breast cancer models are limited in that many do not account for the dynamic transformation of the cancer genome to include the spatiotemporal mutations and genomic rearrangements that inevitably arise as the breast cancer progresses through clonal evolution . Advances in CRISPR gene editing can not only be used to characterize and diagnose breast cancer, but also precisely mimic breast cancer progression at discrete intervals, thus enabling the development of more accurate preclinical models for breast cancer research.…”
Section: Crispr Technology For Breast Cancer Modelingmentioning
confidence: 99%
“…131 However, it is not clear whether these data derived from mouse models adequately recapitulate the human disease in terms of drug delivery to brain tumors. 208 Recent data suggest that gadolinium-DTPAimpermeable cerebral breast metastases have significantly more proliferative nuclei compared to gadolinium-DTPA-permeable tumors in the mouse brain. 209 In contrast, another study showed that melanoma metastases having a permeable vasculature grow faster than those having an intact BTB.…”
Section: Vascularization and The Blood-tumor Barrier Of Metastatic Brmentioning
confidence: 99%